Brazil : Financial Sector Assessment Program-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2018)
The Central Bank of Brazil (BCB) has shown a determined commitment to enhancing its standards and practices of banking supervision. Changes in the thinking and practices of the BCB's supervision are not limited to responses to the demands of the international regulatory reform agenda. Overall, the BCB has been guided by the principle of integration, both in terms of the expectations that it places on its own internal operations but on the standards it expects the financial institutions to meet in governing their own risks and activities. One example is the BCB's innovative and challenging work in the field of contagion analysis at the systemic level which is a perspective it also seeks to embed in its analysis of contagion risk in its prudential work at firm level. Boosting staff levels in conduct supervision, introducing a form of twin peaks, contagion risk analysis, and the prudential conglomerate approach also exemplify welcome developments.